2014
DOI: 10.2133/dmpk.dmpk-13-rg-012
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Glucuronidation of Resveratrol and Pterostilbene: Altered Enzyme Specificity and Potential Gender Differences

Abstract: Summary Resveratrol, a natural polyphenol found in grapes, berries and other plants, has been proposed as an ideal chemopreventative agent due to its plethora of health promoting activities. However, despite its lofty promise as a cancer prevention agent its success in human clinical trials has been limited due to its poor bioavailability. Thus, interest in other natural polyphenols is intensifying including the naturally occurring dimethylated analog of resveratrol, pterostilbene. The UDP-glucuronosyltransfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 37 publications
6
63
0
Order By: Relevance
“…K m values ranged from 0.029 to 0.13 m m , with an overall mean of 0.046 m m . These K m values are consistent with those reported previously …”
Section: Resultssupporting
confidence: 93%
“…K m values ranged from 0.029 to 0.13 m m , with an overall mean of 0.046 m m . These K m values are consistent with those reported previously …”
Section: Resultssupporting
confidence: 93%
“…following topical administration of Pter, Pter-sulfate and Pter-glucuronide (main Pter-derived metabolites generated under in vivo conditions [39]) increased in the skin. Using pooled human liver microsomes, it was shown that glucuronidation of Pter is much less efficient than that of Resv, thus suggesting that Pter may have decreased metabolism in humans [19]. A fact in favor of the higher bioavailability of Pter versus that of Resv.…”
Section: Pterostilbene Metabolism and Bioavailability In The Skin Andmentioning
confidence: 99%
“…Pterostilbene, has a more favorable pharmacokinetic profile [15][16][17]. Pter contains two methoxy groups and one hydroxyl group while Resv has three hydroxyl groups, in consequence Pter is less susceptible to conjugation metabolism and, thus, a longer halflife is expected [18,19]. The dimethoxy structure of Pter enhances its lipophilicity thus increasing membrane permeability and improving its bioavailability [11,16,18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Low bioavailability of resveratrol (3,4',5-trihydroxy-trans-stilbene) upon ingestion resulting from extensive intestine and hepatic conversion to sulphates and glucuronides prompted search for natural or synthetic derivatives with improved pharmacokinetic properties (Ndiaye et al, 2011, Lin et al, 2011, Dellinger et al, 2014.…”
Section: Introductionmentioning
confidence: 99%